Inhibiting Factors for Agents of Change in Promoting Organizational Culture Transformation in the Balikpapan City Government - Aditya, Dina Yuni; Apriani, Fajar; Indarto, Kus (Syntax Literate, 2025)
The government faces complex challenges in achieving development targets amidst the digital era and disruption. Bureaucratic reform serves as the primary strategy for establishing adaptive, clean, and public service-oriented governance. One of the central focuses is the transformation of organizational culture, which involves changing mindsets and work cultures. Within the Balikpapan City Government, agents of changes have been appointed to act as catalysts in implementing organizational culture transformation. However, evaluation results reveal that the existing agents of changes have not yet achieved tangible results in mobilizing changes in organizational culture, and thus, no concrete changes are evident in the implementation of bureaucratic reform. This study aims to analyze the factors that inhibit agents of changes from driving organizational culture transformation. Utilizing a qualitative descriptive approach, data were collected through in-depth interviews with relevant officials and agents of changes, as well as official documents. The research identifies the primary inhibiting factors as a conservative organizational culture, resistance to change, lack of leadership support, limited resources, and restricted authority. These findings indicate the need for strengthened leadership, strategies to overcome resistance, additional resources, enhanced capacities and authority of agents of changes, and more targeted organizational culture reform to support the success of bureaucratic transformation.